Systemic leukofiltration does not attenuate pulmonary injury after cardiopulmonary bypass. - Warren, O; Tunnicliffe, C; Massey, R; Wallace, S; Smith, A; Alcock, E; Darzi, A; Vincent, C; Athanasiou, T (2008)
Pulmonary injury mediated by activated leukocytes is a recognized complication of cardiopulmonary bypass. The aim of this paper is to systematically analyze the effects of systemic leukofiltration within the cardiopulmonary bypass circuit on pulmonary injury and related clinical outcomes. We performed a systematic search to identify randomized controlled trials reporting on the effects of systemic leukofiltration on respiratory parameters. Random effect meta-analytical techniques were applied to identify differences in outcomes between the two groups. Sensitivity and subgroup analyses were undertaken to evaluate study heterogeneity. Incorporating 995 patients, 21 studies satisfied the inclusion criteria. Systemic leukofiltration significantly increased the PaO2/FiO2 ratio within 12 hours of bypass cessation, (weighted mean difference (WMD), 25.97; 95% confidence interval (CI), 3.41-48.53; p = 0.02) but this effect was lost by 24 hours (WMD, 12.98; 95% CI, -7.93-33.89; p = 0.22). Leukofiltration significantly reduced the duration of ventilatory support postoperatively (WMD, -2.11 hours; 95% CI, -0.65 to -3.58; p = 0.005), but had no impact on postoperative chest infection, intensive care length of stay or hospital length of stay. The heterogeneity of the included studies was high, due to poor quality study design and failure to include patients at high risk of pulmonary complications. Systemic leukofiltration may attenuate bypass-related lung injury in the early postoperative period, but this does not seem to translate to clinically significant differences in outcomes.